Effectiveness of Breastfeeding Assistance Model for Pregnant Women, Maternity Women, and Breastfeeding Mothers in West Tulang Bawang Regency in 2023 - Indrasari, Nelly; Mugiati, Mugiati; Risneni, Risneni; Berliana, Eva; Nurlaila, Nurlaila (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Breast milk is the gold standard baby food, breast milk is proven to have advantages that cannot be replaced by any food and drink, because breast milk contains the most appropriate, complete nutrients, and always adjusts to the needs of babies at any time. The gold standard of infant food begins with IMD, followed by exclusive breastfeeding for 6 (six) months (Munzia, 2013).Only 3.7% of infants in Indonesia are breastfed within the first 1 hour after birth. Breastfeeding is recognized as one of the most powerful influences on child survival, growth, and development. Exclusive breastfeeding can reduce the mortality rate of children under five by about 20%. Early initiation of breastfeeding will also greatly help achieve MDGs goal number four of reducing child mortality, as early breastfeeding within the first hour after delivery will reduce newborn mortality. The failure of mothers to breastfeed their babies until six months of age is actually only one problem, which is that mothers do not fully understand the correct way to breastfeed, including techniques and ways to obtain breast milk, especially when they have to work. Understanding IMD and exclusive breastfeeding is a very important issue. IMD and exclusive breastfeeding are possible if individuals, families, health workers and communities understand the meaning, benefits and goals of IMD and exclusive breastfeeding (Munzia, 2013).The results of the 2018 Basic Health Research stated that the exclusive breastfeeding rate for 6-month-old babies in Lampung Province only reached 37.3% of the target of 60%. Meanwhile, in West Tulang Bawang District, the achievement of exclusive breastfeeding was 29.1% of the target of 60%, the achievement of IMD 1 hour 1.8% and IMD 1 hour 39.6% which should be done in all newborns (Riskesdas, 2018).The purpose of the study was to determine the application of the Breastfeeding Model in pregnant women, delivery mothers, and postpartum breastfeeding mothers in West TulangBawang Regency in 2023. This research method uses quasi experiment with pretest-posttest group design. The intervention provided is assistance to pregnant women, laboring women and postpartum breastfeeding mothers who are willing to be assisted and in accordance with the inclusion and exclusion criteria. Before providing assistance, health cadres were trained and provided with knowledge about breastfeeding by the research team in accordance with the research design that had been prepared. The breastfeeding preparation assistance process for pregnant women was carried out during mother's class or according to the free time of pregnant women. The IMD and breastfeeding preparation assistance process was carried out at the place where the mother gave birth for approximately 120 minutes until the end of the postpartum period.The mentoring process is carried out for approximately 6 months by applying the breastfeeding model that has been obtained from the first year of research with a research instrument in the form of a Pocket Book that adapts to the conditions of the respondents. Furthermore, the alternative methods of mentoring will be outlined in a guidebook for pregnant women mentoring models. The population in this study were all pregnant women, laboring mothers, and postpartum breastfeeding mothers in the work area of the West Tulang Bawang District Health Office in 2023. The sample of this study were 30 pregnant women, 30 mothers in labor and 30 postpartum breastfeeding mothers at the Puskesmas in the working area of the West Tulang Bawang District Health Office in 2023 with a total of 90 people. This research is planned to be published in Scientific Journals and Accredited Proceedings, become teaching materials and will be registered as Intellectual Property Rights (IPR). The Technology Readiness Level (TKT) of this research is at level 3 with readiness at this stage at level 2-3.